Business Process Re-engineering to Support Sustainability of The Sales Commodities in Large Transaction with Quotation System - Budiman, Kholiq; Subhan, Subhan; Efrilianda, Devi Ajeng (Universitas Negeri Semarang, 2021)
Purpose: COVID-19 pandemic has an impact in almost all sectors, including economic and industrial sectors. The aim of this research is to support the sustainability of the sales commodities in large transactions due to pandemic conditions by business process re-engineering.Â Methods: Using the moving average method as a forecasting method.Â Result: It can get sustainable sales even during the COVID period, even seen an increase in transactions in the new period, along with the implementation of the quotation information system applied in the re-engineering business process.Â Novelty: Business Process Reengineering as an engineering process to integrate the ERP and the bidding system or quotation system is needed.